Transformational Leadership And Radical Innovation In Industry: A Literature Review - Hutabarat, Rinsan; Tukiran, Martinus; Pratiwi, Ika; Subur, Jumadi (International Journal of Science, Technology & Management, 2023)
Leadership style can be defined as a behavior and strategy resulting from acombination of philosophies, skills, traits and attitudes often applied by aleader when trying to influence the performance of his subordinates.Transformational Leadership is a leadership style in which the leader canidentify needed change, create a vision to guide change through inspirationand execute change with the commitment of group members. Similarly,innovation is a research, development and engineering activity that aims todevelop practical applications, values, and contexts of new science or newways to apply existing science and technology to a product or production.Radical innovation is a new product, service or technology developed by anorganization that completely replaces a company's existing products, servicesand technology. The role of Leadership is very necessary considering thatLeadership is considered one of the important factors influencing innovationbecause leaders influence organizational characteristics and motivatecreativity in their followers, including Industry. A thorough understanding ofstate-of-the-art of Transformational Leadership and Radical Innovation is stillneeded. Therefore, this article aims to classify, identify scientific publicationsand conduct a thematic analysis of the current literature to create an extensiveand detailed understanding of Transformational Leadership and RadicalInnovation, especially in Industry.